Ethnographic Analysis of Nexus about Migration and Culture in Global Perspective - Taukeer, Mohammed (Border Crossing, 2023)
Labour migration from India to Gulf countries is the result of the consequence of globalization by process, determinants and consequences in the first century. Therefore, the present study is based on the study of the nexus of migration and culture in the context of labour migration from Uttar Pradesh to Gulf countries under an ethnographic approach through conducting field works in Uttar Pradesh as root, Mumbai as transit destination and United Arab Emirates as the international destination from November 2017 to December 2019. The findings of the study show that there is an interconnection between internal and international migration by penetration of globalization of culture of migration from Uttar Pradesh to the Gulf via Mumbai. These consequences developed as a safe zone concept of migration due to the depth penetration of cultural migration from Uttar Pradesh. The consequences of the safe zone concept may be defined as the depth penetration of the culture of migration from India to Gulf countries as the consequence of globalization.